Information Technology and Traditional Journalism - Maulet З.; Toktarbai Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The article discusses the basics of accessing electronic equivalents’ names into our database. Today, the new information technology is rapidly developing and changing, and has become a public institution. Under the influence of new information technology, traditional journalism has been developing along with new media, with new trends. In the article, the authors will discuss in detail the interactive nature of the unique features of modern journalism and the role of an individual in the journalist. One of the most important features of information technology is interactive. This interactive character has led to the rejection of the concept and principles of the linear model of science about the sciences.